Nulidad de las Resoluciones Nos. 128 y sin número del 17 de julio de 1950 y 14 de febrero de 1951 - Prieto, Antonio José (Estudios de Derecho, 1956)
Nulidad de las Resoluciones Nos. 128 y sin número del 17 de julio de 1950 y 14 de febrero de 1951